Letter from a stranger - Bradford, Barbara Taylor (London : Harper, 2012)
When award-winning film maker Justine Nolan returns to her beautiful childhood home, she is intrigued by an envelope she finds in her absent mother's post. But the letter inside contains a shocking revelation. If genuine it will change everything she believes about her family's recent history, her mother and her adored grandmother, Gabriele.
Includes bibliographical references.
Keywords: American fiction; Women motion picture producers and directors -- Fiction; Family secrets -- Fiction